Hermann Ebbinghaus y su obra - Sprung, Lothar (1986)
Uber das Gediichtnis: Untersuchungen zur experimentellen Psychologie by Hermann Ebbinghaus, is the "birth announcement" of the psychophysics of higher cognitive pro· ccsses. This is a memorial paper about Ebbing· haus. lt gives sorne informations about his life, work and impact. Ebbinghaus' work is connected with two laws in memory, two new methods in the topic of memory research, a test of intelligence for children, sorne researches in perception, etc. He founded laboratories of experimental psychology at the universities of Berlin, Breslau and Halle. Last but not least he founded the important Zeitschrift für Psychologie und Physiologie der Sinnesorganein 1890.